Starting small to communicate - Alp Atakan; Levent Koçkesen; Elif Kubilay (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
We analyze a repeated cheap-talk game in which the receiver is privately informed about the conflict of interest between herself and the sender and either the sender or the receiver controls the stakes involved in their relationship. We focus on payoff-dominant equilibria that satisfy a Markovian property and show that if the potential conflict of interest is large, then the stakes increase over time, i.e., "starting small" is the unique equilibrium arrangement. In each period, the receiver plays the sender's ideal action with positive probability and the sender provides full information as long as he has always observed his ideal actions in the past. We also show that as the potential conflict of interest increases, the extent to which the stakes are back-loaded increases, i.e., stakes are initially smaller but grow faster.
Keywords: D82; D83; D23; 330; Communication; Cheap Talk; Reputation; Repeated Games; Career Path; Gradualism; Starting Small